Contextual theologies and orientalism: a case study of a selection of iranian muslim weblog - Ghanian, Mahdie (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Anti-Muslim sentiment has been intensified since 11 September, in which Muslims are often considered as ‘others’, ‘terrorist’ or ‘violent’. Although we are exposed every day about Muslims in general from media in the West we know a little about these issues from the eyes of an insider and how Muslims themselves narrate their religion. Cyberspace has created a new cultural space for public discourse through languages. Methods: This research investigates Muslim voices in cyberspace to show how Iranian Muslims represent their religion on their weblogs. The narratives of ten blogs written by Iranian Muslims were analyzed through qualitative content analysis. The theoretical framework of this study is based on Edward Said's Orientalism Theory. Target blogs are written in English or Persian language. Findings: The result displays that although Iranian bloggers live in various Western countries, such as Germany, England, Canada, and the United States; they narrate and share their Shia culture and identity in their virtual pages. Conclusion: This research highlights how Iranian Muslims use blogs as a platform to represent their faith and culture, challenging the stereotypes and misconceptions prevalent in the West. Novelty/Originality of This Study: The study provides insights into how Iranian Muslims utilize cyberspace to narrate their own religious and cultural experiences, offering a perspective that contrasts with the often negative portrayal of Muslims in Western media.